2008
DOI: 10.1089/jmf.2008.0059
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of White and Pink Grapefruit Juice with Acetaminophen (Paracetamol)In Vivoin Mice

Abstract: Grapefruit juice increases bioavailability of a number of drugs because of inhibition of the P-glycoprotein pump and inhibition of intestinal cytochrome P450 3A4 enzyme. However, interaction between acetaminophen (also known as paracetamol in many parts of the world) and grapefruit juice has never been reported. The interaction of grapefruit juice with acetaminophen was examined in an in vivo mouse model. BALB/c mice were fed 200 microL of white grapefruit juice or pink grapefruit juice by oral gavage (three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
1
7
1
Order By: Relevance
“…These findings are in line with the observed increase in paracetamol plasma concentrations. However, contrary to our present results and those of Dasgupta et al, Qinna et al found that frequent administration of GFJ reduced the oral bioavailability of paracetamol in rats (19)(20)(21). This discrepancy might be related to species differences.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings are in line with the observed increase in paracetamol plasma concentrations. However, contrary to our present results and those of Dasgupta et al, Qinna et al found that frequent administration of GFJ reduced the oral bioavailability of paracetamol in rats (19)(20)(21). This discrepancy might be related to species differences.…”
Section: Discussioncontrasting
confidence: 99%
“…GFJ-paracetamol interaction has not drawn a lot of attention because of the small portion of paracetamol that undergoes cytochrome P450 enzymes metabolism. Dasgupta et al and Samojlik et al have shown that GFJ increased the concentrations of paracetamol in mice compared with the control after single and multiple doses, respectively (19)(20). On the contrary, Qinna et al reported a reduced bioavailability of paracetamol following multiple GFJ administration in rats and reduced salivary levels of paracetamol in human saliva following a single dose of GFJ (21)(22).…”
mentioning
confidence: 99%
“…These include mainly flavonoids found in fruit juices, vegetables, flowers and tea. Especially grapefruit juice has been shown to interfere with plasma levels of colchicines [54], paracetamol [55], and cyclosporine [56].…”
Section: Importance Of Abc-transporter For Admetmentioning
confidence: 99%
“…For example, acetaminophen/paracetamol (Tylenol) concentrations were found to be increased in murine blood by white and pink grapefruit juice, with the white juice acting faster [13]. Interestingly, "the bioavailability of paracetamol was significantly reduced following multiple GFJ administration" in mice and rats.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, "the bioavailability of paracetamol was significantly reduced following multiple GFJ administration" in mice and rats. This suggests that repeated intake of grapefruit juice reduces the efficacy and bioavailability of acetaminophen/paracetamol in comparison to a single dose of grapefruit juice, which conversely increases the efficacy and bioavailability of acetaminophen/paracetamol [12,13]. Tassaneeyakul et al reported the effect of grapefruit juice intake on the disposition of omeprazole and its primary metabolites, following a single oral dose, to 13 healthy volunteers, two of whom being poor metabolisers for cytochrome P450 (CYP) 2C19 [14].…”
Section: Introductionmentioning
confidence: 99%